CONTENTS OF COMPETENCE IN THE DOMAIN OF OBJECT-ORIENTED PROGRAMMING AND STAGES OF ITS DEVELOPMENT BY BACHELORS OF PEDAGOGICAL EDUCATION USING NETWORK COMMUNITIES - Moglan, Diana V. (Otkrytoe Obrazovanie, 2016)
This article is devoted to the ways of teaching object-oriented programming of bachelors of pedagogical education in network community. The article provides a definition of competence in the domain of objectoriented programming and describes its substantial components. The author presented the content of discipline “Object-Oriented Programming” and described the work of bachelors for the study sections of the discipline in a network community.